Student Perceptions of Lecturer Performance in Enhancing Student Satisfaction in The Islamic Education Management Master's Program at The Faculty of Education and Teacher Training State Islamic University of North Sumatra Medan - Fikri Sholehuddin SN, Abdullah; Santoso, Didik (Innovative: Journal Of Social Science Research, 2025)
This research aims to explore: First, students' perceptions of lecturer performance. Second, students' satisfaction with lecturer performance in the Islamic Education Management Master's Program at FITK, UIN North Sumatra Medan. This research employs a qualitative approach with a phenomenological design. The instruments utilized include observation, interviews, and documentary analysis. The research is conducted in the Islamic Education Management Master's Program at FITK, UIN North Sumatra Medan. Data analysis involves three steps: data reduction, data presentation, and conclusion drawing. The findings reveal that: First, there is a positive perception among students regarding lecturer performance, particularly concerning their teaching abilities, guidance on assignments, and thesis supervision. Lecturers demonstrate competence in teaching within their expertise and course materials. Moreover, they create a supportive and nurturing teaching environment. Specifically in thesis supervision, lecturers provide professional guidance by offering direction and explaining materials that students may find challenging. However, some negative perceptions exist, especially regarding the discipline of lecturers during classes. Some lecturers are occasionally late or fail to notify students in advance when they are unable to conduct the class. Second, students express satisfaction with lecturer performance, feeling that their expectations are met. Despite this, some dissatisfaction remains due to the lack of discipline displayed by lecturers in terms of punctuality and occasional unexplained absences, which diminishes overall satisfaction with lecturer performance.